Vestibulo-ocular reflex in patients with superior semicircular canal benign paroxysmal positional vertigo (BPPV). (May 2014) - Perez-Fernandez, Nicolas; Martinez-Lopez, Marta; Manrique-Huarte, Raquel
Abstract: Conclusion: The function of all the semicircular canals in patients with idiopathic benign paroxysmal positional vertigo (BPPV) in whom otoconial debris is located in the superior semicircular canal (SSC) is normal. Objective: BPPV of SSC is an infrequent entity in which otoconial debris evokes vertigo and nystagmus in the head-hanging position and during anterior flexion of the patient. Methods: We studied the vestibulo-ocular reflex (VOR) in 12 patients with this particular type of BPPV. The reflex was evoked by rapid head impulses in the plane of the three semicircular canals in the affected and the normal ear. The reflex was evaluated with a video system that analyzes the head and eye velocity: the gain (the relation between both magnitudes) was the objective measure. Results: The mean gain of VOR was within normal limits for the six semicircular canals and there were no significant differences between the same canals on each side of patients with BPPV in whom canalolithiasis was located in the SSC. However, gain asymmetry was different for each pair of canals.